PENGARUH PROMOSI DAN HARGA TERHADAP MINAT BELI PERUMAHAN OBAMA PT. NAILAH ADI KURNIA SEI MENCIRIM MEDAN - Muhammad Fakhru Rizky Nasution (Universitas Muhammadiyah Sumatera Utara, 2017)
This study aimed to determine the effect of promotion and price to intention to buy. Sample that observed were 100 respondent that interest and would buy the product. The result showed that promotion and price, partially and simultaneously influence to intention to buy. Determinant coefficient showed that 14,3% variation of intention to buy had influenced by promotion and price.